Experiences integrating teleworking tools in face-toface teaching: satisfaction of students - Vereda-Alonso, Cristina; Cerrillo-González, María del Mar; Gómez-Lahoz, César; García-Delgado, Rafael A.; Rodríguez-Maroto, José Miguel; Vereda-Alonso, Carlos (IATED Academy, 2024)
In another contribution presented at this conference, we outlined the objectives, methodology, and academic results of an Educational Innovation Project conducted at the University of Malaga. The innovations were implemented in three subjects: the fourth-year subject “Treatment of Contaminated Soil” in the Chemical Engineering degree, the first-year subject “Mass Exchange Network for Pollution Prevention” in the Master's degree in Chemical Engineering, and the thirdyear subject “Psycholinguistics Applied to the Study of the English Language” in the English Studies degree. This paper details the evaluation results of this project.
Acceso abierto en https://library.iated.org/view/VEREDAALONSO2024EXP
Keywords: Enseñanza - Innovaciones; Tecnología educativa; Synchronous online presentation; Microsoft Teams; Challenges of moderating